Yang-Baxter deformations of supercoset sigma models with ℤ4m grading *Supported by National Natural Science Foundation of China (11375141, 11425522, 11547050), Natural Science Foundation of Shaanxi Province (2013JQ1011, 2017ZDJC-32, 2016JM1027), Special Foundation for Basic Scientific Research of Central Colleges (310812152001, 310812172001, 2013G1121082, CHD2012JC019), Scientific Research Program Funded by Shaanxi Provincial Education Department (2013JK0628), Xi'an Shiyou University Science and Technology Foundation (2010QN018) and partly supported by the Basic Research Foundation of Engineering University of CAPF (WJY-201506). (November 2017) - Ke 柯, San-Min 三民; Yang 杨, Wen-Li 文力; Jang 江, Ke-Xia 克侠; Wang 王, Chun 春; Shuai 帅, Xue-Min 学敏; Wang 王, Zhan-Yun 展云; Shi 石, Gang 刚
Abstract: We have studied Yang-Baxter deformations of supercoset sigma models with ℤ4 m grading. The deformations are specified by a skew-symmetric classical r -matrix satisfying the classical Yang-Baxter equations. The deformed action is constructed and the Lax pair is also presented. When m =1, our results reduce to those of the type IIB Green-Schwarz superstring on AdS 5 × S 5 background recently given by Kawaguchi, Matsumoto and Yoshida.